After heaven : spirituality in America since the 1950s - Wuthnow, Robert (University of California Press, 1998)
The evolution of American spirituality over the past 50 years is the subject of Robert Wuthnow's book. Wuthnow uses in-depth interviews and a broad range of resource materials to show how Americans, from teenagers to senior citizens, define their spiritual journeys.